Genomic effect of triclosan on the fetal hypothalamus: evidence for altered neuropeptide regulation - Rabaglino, Maria Belen (2016)
Triclosan (TCS), an antibacterial compound commonly added to personal care products, could be an endocrine disruptor at low doses. Although TCS has been shown to alter fetal physiology, its effects in the developing fetal brain are unknown. We hypothesize that exposure to TCS during fetal life could affect fetal hypothalamic gene expression. The objective of this study was to use transcriptomics and systems analysis to identify significantly altered biological processes in the late gestation ovine fetal hypothalamus after direct or indirect exposure to low doses of TCS. For direct TCS exposure, chronically catheterized late gestation fetal sheep were infused with vehicle (n=4) or TCS (250 μg/d; n = 4) iv. For indirect TCS exposure, TCS (100 μg/kg d; n = 3) or vehicle (n = 3) wasinfused into the maternal circulation. Fetal hypothalami were collected after 2 days of infusion, and gene expression was measured through microarray. Hierarchical clustering of all samples according to gene expression profiles showed that samples from the TCS-treated animals clustered apart from the controls. Gene set enrichment analysis revealed that fetal hypothalamic genes stimulated by maternal and fetal TCS infusion were significantly enriching for cell cycle, reproductive process, and feeding behavior, whereas the inhibited genes were significantly enriching for chromatin modification and metabolism of steroids, lipoproteins, fatty acids, and glucose (P<.05). In conclusion, short-term infusion of TCS induces vigorous changes in the fetal hypothalamic transcriptomics, which are mainly related to food intake pathways and metabolism. If these changes persist to postnatal life, they could result in adverse consequences in adulthood.